In The Context of Turkish Culture Animal Symbolism in Heterodox Dervishes - Harmanci, Meric (Rector CIU Cyprus Int Univ, 2022)
The belief systems of societies that have continued since mythical periods exhibit their vestiges in newly accepted religions. The memories of the past and the mythical codes that have been placed in the subconscious of the Turkish society that accepted Islam also find themselves reflected in the cultural assets in an ongoing process. As one cornerstone of this life, animals have had an important place in their mythical worlds and systems of thought, as have many elements that have been included in the cultural world of the Turks, having lived on the nomadic steppes for ages. The animal motifs in the zoomorphic world design of the Turks, in the myths of descent, in the narratives as guides and assistants, overlap with the names of some dervishes in the Sufi literature. In this study, the mythological traces in the naming of dervishes, who are called by the names of some animals, were tried to be determined through animal symbolism in Turkish mythology. At the same time, the characteristics of dervishes who take animal names in the Sufi literature that cause this naming are emphasized. The fact that these dervishes have common characteristics in terms of disposition and that almost all of them are from the group of heterodox dervishes also brings up the relationship between animal symbolism and melamet. At this point, heterodoxy emerged as a form of religious interpretation, which is one of the factors in Turks' acceptance of Islam beyond the central understanding of the religion; it created a syncretic interpretation of Islam by incorporating mysticism. These animal titles, which are preferred to contribute to the systematic of the Melamet doctrine that works to accuse the human soul, can be thought of as a mystic interpretation or traces of a sectarian line. The study also examines the naming in the names of wandering dervishes with animal titles in the center of melamet; naming stories and tries to reveal the symbolic and functional consistency of these titles. In this context, it has been determined that the animal names in the names of sufis such as Asian Baba [Lion Father], Kurt Baba [Wolf Father], Barak Baba [Dog Father], Koyun Baba [Sheep Father], Geyikli Baba [Deer Father] have a function beyond animal symbolism. It has been observed that the negative perception of the world of associations that these animals represent in terms of social and semantics is utilized. This study aims to evaluate how animal symbolism is seen in heterodox dervishes and the animal names in the names of these dervishes through mythical and esoteric readings.
Keywords: symbol; naming; animal symbolism; sufism; heterodoxy; Arts & Humanities - Other Topics; Literature